The Cambridge History of Musical Performance - Lawson, Colin; Stowell, Robin (Cambridge Cambridge University Press, 2012)
The intricacies and challenges of musical performance have recently attracted the attention of writers and scholars to a greater extent than ever before. Research into the performer's experience has begun to explore such areas as practice techniques, performance anxiety and memorisation, as well as many other professional issues. Historical performance practice has been the subject of lively debate way beyond academic circles, mirroring its high profile in the recording studio and the concert hall. Reflecting the strong ongoing interest in the role of performers and performance, this History brings together research from leading scholars and historians and, importantly, features contributions from accomplished performers, whose practical experiences give the volume a unique vitality. Moving the focus away from the composers and onto the musicians responsible for bringing the music to life, this History presents a fresh, integrated and innovative perspective on performance history and practice, from the earliest times to today.
Keywords: Past; Performance; Music history; Europe